2007
DOI: 10.1200/jco.2006.07.9319
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiation Therapy Is Associated With Improved Survival in Merkel Cell Carcinoma of the Skin

Abstract: The use of adjuvant radiation therapy is associated with improved survival in patients with MCC. Prospective evaluation of adjuvant radiation therapy in this setting is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
196
2
16

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(219 citation statements)
references
References 28 publications
5
196
2
16
Order By: Relevance
“…One analysis of the Surveillance, Epidemiology, and End Results database by Mojica et al (19) suggested an improvement in OS with adjuvant RT after surgery. Surgical intervention was a component of therapy in 89% of the cases (n 5 1,487).…”
Section: Discussionmentioning
confidence: 99%
“…One analysis of the Surveillance, Epidemiology, and End Results database by Mojica et al (19) suggested an improvement in OS with adjuvant RT after surgery. Surgical intervention was a component of therapy in 89% of the cases (n 5 1,487).…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based study suggested a survival benefit with adjuvant radiotherapy. 14 Nonetheless, because of small sample sizes and heterogeneous patient populations of MCC series to date, optimal management of this malignancy continues to be controversial.…”
mentioning
confidence: 99%
“…MCC is a radiosensitive malignancy; however, the use of radiotherapy (RT) as monotherapy is typically reserved for patients that are not eligible for surgery (5). Mojica et al (15) reported a median survival time of 63 months for patients who were treated with RT as an adjuvant to surgery, compared with 45 months for those who underwent surgery alone. The treatment of MCC with chemotherapy remains under evaluation.…”
Section: Nuclear Medicine Techniques In Merkel Cell Carcinomamentioning
confidence: 99%